Immunomodulatory therapy to achieve maximum efficacy: doses, monitoring, compliance, and self-infusion at home. - Lucas, M; Hugh-Jones, K; Welby, A; Misbah, S; Spaeth, P; Chapel, H (2010)
INTRODUCTION: The Oxford Programme for Immunomodulatory Immunoglobulin Therapy has been operating since 1992 at Oxford Radcliffe Hospitals in the UK. Initially, this program was set up for patients with multifocal motor neuropathy or chronic inflammatory demyelinating poly-neuropathy to receive reduced doses of intravenous immunoglobulin (IVIG) in clinic on a regular basis (usually every 3 weeks). The program then rapidly expanded to include self-infusion at home, which monitoring showed to be safe and effective. It has been since extended to the treatment of other autoimmune diseases in which IVIG has been shown to be efficacious. METHODS: This review includes details of the program such as the training of patients, dosing with immunoglobulin, and monitoring and compliance for self-infusion at home, with cases to illustrate these points. RESULTS: In addition, the Evidence for efficacy and the effects of confounding morbidities will be are included described. More recently, subcutaneous immunoglobulin therapy (SCIG) has been used in several chronic autoimmune peripheral neuropathies and in epidermolysis bullosa acquisita, with equally good effect. Trials of SCIG in other autoimmune diseases are planned.